EXTENT OF CYANIDE, NITRATE, AND FLAVONOIDS GOITROGENS IN SOILS AND TOBACCO PLANT IN SOKOTO, NIGERIA - Umar, AI; Sarkingobir, Yusuf; Tambari, Umar; Salau, Ibrahim Alhaji; Aliyu, Sulaiman; Gobir, Shehu Sarkin; Miya, Yusuf Yahaya (GeoEco, 2023)
Nitrate, cyanide, and flavonoids are among the chemicals that threatens hormones especially the thyroid gland and in turn affecting the body. Their presence in tobacco and cigarette shall be determine to inform the public. The objective of this work was to determine the extent of nitrate, cyanide, and flavonoids in soil and tobacco from Sokoto, Nigeria using standard methods. The results determined by this work indicated varied levels of goitrogens (cyanide, nitrate, and flavonoids) present in soils and tobacco leaves grown in three different points within Sokoto state, Nigeria (namely, Sokoto city, Gwadabawa, and Illela). 100.21±6.12 -705.10±4.60ppm, ppm 136± 6.10-170.30±3.36ppm, 7.10±0.3-17.0±0.11ppm are range values of cyanide, nitrate, and flavonoids respectively obtained in soils in Sokoto state. Likewise, 90.0±2.16-500.0±1.3ppm, 70.11±3.9-120.0±10.3ppm, 6.2±0.5-25.11±0.05ppm are the ranges of cyanide, nitrate, and flavonoids respectively determined in tobacco leaves in Sokoto state, Nigeria. There exist elevated levels of the goitrogens in soils and tobacco in Sokoto, therefore, risking the consumers and non-consumers to iodine deficiency.